2022
DOI: 10.1021/acs.jmedchem.2c00413
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Potent STAT3 Inhibitor HP590 with Dual p-Tyr705/Ser727 Inhibitory Activity for Gastric Cancer Treatment

Abstract: Accumulating evidence has documented that STAT3 phosphorylation at Tyr705 and Ser727 jointly promotes the initiation and progression of gastric cancer. However, most reported STAT3 inhibitors have mainly focused on suppressing STAT3 phosphorylation at Tyr705 while ignoring the tumorigenic effects of phosphorylation at Ser727. Herein, we described the design, synthesis, and structure–activity relationship studies on a series of triaromatic heterocyclic derivatives as potent dual phosphorylation STAT3 inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…To assess the MYC engagement of 37 in native cellular environment, cellular thermal shift assay (CETSA), a new method based on the ligand-induced alteration in protein thermal stability, was employed in subsequent functional investigation (Figure A) . The results demonstrated that MYC expression in DMSO-treated PC-3 cells declined continuously as the incubation temperature increased.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the MYC engagement of 37 in native cellular environment, cellular thermal shift assay (CETSA), a new method based on the ligand-induced alteration in protein thermal stability, was employed in subsequent functional investigation (Figure A) . The results demonstrated that MYC expression in DMSO-treated PC-3 cells declined continuously as the incubation temperature increased.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the STAT family of proteins on IBD pathology is also an area of active investigation. No clinical trials have been undertaken for the treatment of IBD to date, although the pharmacokinetics and safety/tolerability of inhibitors targeting dual phosphorylation or the SH2 domain of STAT3 have been evaluated in patients with solid tumors and natural killer/T-cell lymphoma ( 55 – 59 ) (ClinicalTrials.gov no: NCT03240939). As technology advances, such as for the degradation of STAT proteins, more drugs targeting STAT could enter clinical development, adding to the IBD treatment armamentarium ( 60 ).…”
Section: Stat Inhibitorsmentioning
confidence: 99%
“…CYP Inhibition Assay. As previously reported, 49 the inhibition potency of HP661 for the CYP450 enzyme was evaluated by human liver microsomes (HLM). IC 50 values were calculated with GraphPad Prism software version 8.0.…”
Section: Synthesis Of 5-((5-methyl-4-(4-(methylsulfonyl)piperazine-1-...mentioning
confidence: 99%